Comparison between power off-ice test and performance on-ice anaerobic testing - Boucher, V. G.; Parent, A. A.; Miron, F. S. J.; Leone, M.; Comtois, A. S. (The Journal of Strength and Conditioning Research, 2020)
The importance of specific testing has been shown in ice hockey performance, and the understanding and connection between them may lead to adapting training and follow-up in elite athletes. The aim of this study was to compare 2 off-ice power tests with performances on ice with National Hockey League (NHL) players. The vertical jump and broad jump tests were used for the off-ice evaluations, whereas a modified SAS-40 and a repeated-sprint skate (RSSm) test were used on-ice as performance variables. Thirty-one players (3 goalkeepers, 10 defense players, and 18 forward players) from the NHL performed before preseason training camp. Four evaluation sessions were performed with 48-hour time intervals between them. The results show that the 2 jump types were correlated (r2 = 0.45 p < 0.01), and there was a significant correlation between the vertical jump and the best SAS-40 time trial for defense players, but not for forward players (r2 = 0.76 p = 0.02; r2 = 0.21 p = 0.16, respectively). By contrast, there was a significant correlation between broad jump and best SAS-40 time trial for forward players but not for defensive players (r2 = 0.75 p < 0.01; r2 = 0.19 p = 0.28, respectively). In conclusion, results show that specific player ability needs to be taken into consideration when choosing off-ice tests.